A review of Italian research on free-living marine nematodes and the future perspectives on their use as Ecological Indicators (EcoInds) - SEMPRUCCI, F.; LOSI, V.; MORENO, M. (Mediterranean Marine Science, 2015)
The use of free-living marine nematodes as ecological indicators (EcoInds) of human impacts has increased greatly in Italy since 1990. This paper is a summary of the Italian research experience in the study of nematode assemblages of shallow water habitats, and provides a breakdown of the most important insights that have been obtained so far. Although nematodes are among the best candidates for the Ecological Quality (EcoQ) assessment in the benthic domain, many guidelines need to be developed and limits overcome. Italian research has certainly contributed to the achievement of this purpose with highly focused local investigations on the effects of specific stressors (riverine and sewage discharge, aquaculture, trace elements and hydrocarbons), but also to a large extent with wider analyses aimed at finding new and valuable tools for monitoring programs and useful nematode descriptors, in line with the European Directives. Currently, the Italian and foreign experiences in this field draw light to the fact that the best nematode descriptors for the EcoQ assessment are the taxonomic composition and life strategy traits. However, nematode worldwide research is running the risk of being marginalized because of the relatively narrow scope of most contemporary studies. Nematode researchers should work in a nematologist community in order to better promote the use of nematodes such as EcoInds in the era of the Water Framework Directive (WFD) and Marine Strategy Framework Directive (MSFD). In the present paper, possible steps to obtain this goal are brought to the reader’s attention and discussed.